Evaluating the implementation of hospital management information systems based on the DeLone and McLean model: A systematic review - Teguh Ariyanto; Budi Aji; Arih Diyaning Intiasari (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The evaluation of information system success continues to attract attention from researchers, practitioners, and management stakeholders alike. Gaining a clear understanding of this success is essential, as it underscores the system’s value and informs future decision-making related to its implementation and improvement. Several methods exist for measuring information system (IS) success, with the DeLone and McLean IS Success Model (D&M model) being the most widely recognized and validated framework. Purpose: To evaluate the effectiveness of Hospital Information Systems (HIS) based on the DeLone and McLean Information Systems Success Model in various healthcare settings. The research focuses on identifying key success factors, challenges in adoption, and implications for future HIS implementations. Method: A systematic review was conducted across five articles published between 2017 and 2024, sourced from Saudi Arabia (1 paper, 20%), Nigeria (1 paper, 20%), South Africa (1 paper, 20%), and Indonesia (2 papers, 40%). The articles were assessed using the DeLone and McLean model, which includes six core dimensions: system quality, information quality, service quality, user satisfaction, usage, and net benefits. Data were collected through user satisfaction surveys, Structural Equation Modeling (SEM), and Partial Least Squares (PLS) techniques. A total of 2,441 participants were involved, including 1,784 healthcare professionals and 657 health information management staff. Results: Findings show that system quality is the most significant factor influencing HIS success, with a positive correlation coefficient of 0.87 between system quality and user satisfaction (p < 0.01). A study in South Africa demonstrated that information quality significantly influenced system usage (β = 0.65, p < 0.05), while service quality impacted user satisfaction with a coefficient of 0.73 (p < 0.01). In Nigeria, although system quality was associated with net benefits (β = 0.53, p < 0.01), user satisfaction did not directly correlate with these benefits (p > 0.05). Common adoption challenges included network disruptions and data storage problems, which were reported in 35% of hospitals using SIMRS in Indonesia. Conclusions: For future HIS implementations to succeed, healthcare institutions must prioritize improving system quality, enhancing information quality, and strengthening service quality. Addressing technical and training challenges will be crucial in overcoming adoption barriers and ensuring the long-term success of HIS.